THE PERCEPTION OF SMS ADVERTISING INTRUSIVENESS DIFFERS BETWEEN AGE GROUP - Mahiah Binti Said; Shari Md. Nor (Journal of Management and Business, 2010)
hort messaging system (SMS) has overtaken the means of communicating and interacting between individuals today, regardless of age, gender, social class and boundaries. Organizations around the world today have incorporated SMS into their strategic marketing communication plans as one vital tool to reach out to their target customers. It rapidly becomes a vital media vehicle since it has precision targeting, personalization, customization and measurability, impact, persuasiveness and interactivity. Age is a widely used demographic variable to characterize the adoption of technologies between two or more consumer groups (Morris and Venkatesh, 2000). There are certain differences exist in their behavior because of their inherent motivational needs. This paper is looking at the perceptions of different age group towards the intrusiveness of SMS advertising and how their perception could affect their brand loyalty and purchase intention. 550 questionnaires were distributed to mobile phone users using systematic stratified random sampling method.